A shared space for emotion: A poetic inquiry into Indonesian EFL students’ language learning experiences - Fauziah Fauziah; Jamaliah Jamaliah; Novita Diana (Siliwangi University, 2025)
This poetic inquiry aims to explore Indonesian EFL students’ experiences and emotional landscapes in their English language learning process. In this study, eighteen Indonesian EFL non-English major university student participants were recruited following the ethical protocols. Data were collected through a combination of poetry and interviews, capturing a shared space where feelings, struggles, and aspirations can be voiced and collectively understood. A thematic analysis identified patterns and recurring themes in the poetry and interviews, enabling the participants to openly express how positive and negative emotions such as anxiety, pride, and hope shape their engagement with English and their evolving sense of self as language learners. The poetic process not only served as an interpretive method but also as an empathetic medium that honors participants’ voices while revealing the relational and affective dimensions of language learning. The study demonstrates how poetic inquiry functions not only as a representational device but also as an interpretive and relational methodology that enables nuanced access to learners’ affective worlds. By foregrounding poetic inquiry as both methodological and pedagogical practice, this research contributes to expanding approaches for understanding emotional and experiential dimensions of language learning in EFL contexts. Keywords: EFL learning experience, emotion, innovative pedagogy, poetic inquiry, poem